2017
DOI: 10.1002/ccr3.803
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of LH cause virilization in a postmenopausal woman

Abstract: Key Clinical MessageSome testosterone‐producing adrenal tumors can be successfully treated with long‐acting GnRH analogs and adrenal venous sampling can be useful to detect rare ectopic sex steroid‐producing tumors or confirm bilateral adrenal androgen hyperproduction in female hyperandrogenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Then as a trial, Lupron may cause decline in the level of testosterone, giving an impression of gonadotropin-responsive testosterone-secreting ovarian tumor. Lupron is a GnRH agonist, which on constant presence by depo causes ovarian depression after initial brisk stimulation [7]. Later on, bilateral laparoscopic salpingo-oophorectomy and excisional biopsy revealed left stromal luteoma, bilateral stromal hyperthecosis and right paratubular cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Then as a trial, Lupron may cause decline in the level of testosterone, giving an impression of gonadotropin-responsive testosterone-secreting ovarian tumor. Lupron is a GnRH agonist, which on constant presence by depo causes ovarian depression after initial brisk stimulation [7]. Later on, bilateral laparoscopic salpingo-oophorectomy and excisional biopsy revealed left stromal luteoma, bilateral stromal hyperthecosis and right paratubular cysts.…”
Section: Discussionmentioning
confidence: 99%
“…A review of androgen-secreting adrenocortical tumors reported free testosterone >6.85 pg/mL had the best sensitivity (82%) and specificity (97%) but there is clinical overlap [9]. Adrenal tumors are frequently gonadotropin-independent, although exceptions exist [10]. Ovarian malignancy also tends to be gonadotropin-independent, but basal hormone measures are not sufficient for diagnosis.…”
Section: Editorialmentioning
confidence: 99%
“…However, the prevalence of disease favors an ovarian over adrenal androgen source. GnRH agonist testing cannot differentiate adrenal and ovarian etiologies; dexamethasone suppression testing may help [10]. It is crucial for providers to differentiate between hormonal changes of normal aging and pathological cause of hyperandrogenism.…”
Section: Editorialmentioning
confidence: 99%